Maternity Nurses' Knowledge about Sudden Unexpected Postnatal Collapse and Safe Newborn Positioning. Issue 2 (March 2020) - Addison, Camilla; Ludington-Hoe, Susan
Abstract: Purpose: Sudden unexpected postnatal collapse (SUPC) of healthy newborns in the first 2 days of life is increasing. These types of adverse events are known to be associated with unsafe positioning during skin-to-skin contact and breastfeeding. The purpose of the study was to determine maternity nurses' knowledge about SUPC and safe newborn positioning. Design: Nurses who participate in a hosted listserv were solicited to complete a questionnaire. Methods: An email with an embedded link to a 20-item questionnaire, the SUPC and Safe Positioning Knowledge Assessment Tool, and 16 demographic questions was sent to 605 maternity nurses in the United States who are part of a Perinatal Listserv for members of the Association of Women's Health, Obstetric and Neonatal Nurses. Scores were analyzed by mean, standard deviation, and percent correct answers. Results: Fifty questionnaires were initiated (response rate of 8.2%), and 36 completed questionnaires (response rate of 5.9%) were analyzed. Maternity nurses' knowledge of SUPC was less than their knowledge of safe newborn positioning (61% correct vs. 72% correct; p < 0.001). Clinical Implications: Maternity nurses need more information about SUPC and safe newborn positioning, including risk factors, and effective strategies to reduce risk of preventable newborn harm. Abstract : Rooming-in, skin-to-skin contact, and breastfeeding are common practices in the newborn period. Yet, skin-to-skin contact and breastfeeding have been associated with an increase in sudden unexpected postnatal collapse in healthy newborns, which commonly occurs when the newborn's airway becomes obstructed. An overview of sudden unexpected postnatal collapse is presented along with results of a survey of nurses' knowledge of these types of events.